Juvenile rheumatoid arthritis. Effects of disease activity and recombinant human growth hormone on insulin-like growth factor 1, insulin-like growth factor binding proteins 1 and 3, and osteocalcin. - Davies, U; Jones, J; Reeve, J; Camacho-Hubner, C; Charlett, A; Ansell, B; Preece, M; Woo, P (1997)
OBJECTIVE: To investigate possible mechanisms of growth impairment in children with juvenile rheumatoid arthritis (JRA). METHODS: Eighteen prepubertal children with JRA and growth retardation received recombinant human growth hormone (rHuGH) for 1 year. Growth hormone profiles over 24 hours were obtained before treatment in 12 patients; the levels did not differ from those in "short normal" children. Levels of insulin-like growth factor 1 (IGF-1), IGF binding proteins (IGFBPs) 1 and 3, insulin, osteocalcin, and C-reactive protein (CRP), as well as the erythrocyte sedimentation rate were measured serially. Pretreatment levels were compared with control levels. RESULTS: In JRA patients, IGF-1, IGFBP-3, and osteocalcin levels were significantly lower and insulin levels significantly higher than those in controls, but there was no significant difference in the level of IGFBP-1. With rHuGH treatment, height velocity and mean levels of IGF-1, osteocalcin, and insulin increased significantly, while mean levels of IGFBP-1 fell significantly. Levels of IGFBP-3 correlated with those of IGF-1. The height velocity correlated positively with IGF-1 and osteocalcin, and negatively with IGFBP-1. Levels of IGFBP-1 were inversely related to those of insulin and IGF-1. There was a significant negative correlation between the CRP and height velocity, IGF-1 level, and osteocalcin level. CONCLUSION: IGF-1 production is impaired in children with active JRA. Treatment with a therapeutic dose of rHuGH can rectify the IGF-1 deficiency within 4 days, but its effect is adversely influenced by the acute-phase response, as reflected by an elevated CRP level.